2022
DOI: 10.1021/jacs.2c02777
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Cations Critically Affects Water at the Negatively Charged Silica Interface

Abstract: Understanding the collective behavior of ions at charged surfaces is of paramount importance for geological and electrochemical processes. Ions screen the surface charge, and interfacial fields break the centro-symmetry near the surface, which can be probed using second-order nonlinear spectroscopies. The effect of electrolyte concentration on the nonlinear optical response has been semi-quantitatively explained by mean-field models based on the Poisson−Boltzmann equation. Yet, to explain previously reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 68 publications
4
39
0
Order By: Relevance
“…By studying ion adsorption with and without background salts, we show that -OH region SFG signal is not always an ideal probe to infer ion adsorption, due to the ambiguity created by multiple effects, such as the hydration shell of the ions or interference effects. 30,[34][35] On the other hand, XFNTR cannot provide some details of ion distribution, because it is sensitive only to the total number of ions in both Stern and diffuse layers and insensitive to the reorganization of ions 4 between them. 28 Acknowledging the advantages and shortcomings of both methods allows elucidating the details of trivalent ion adsorption that cannot be determined by a single method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By studying ion adsorption with and without background salts, we show that -OH region SFG signal is not always an ideal probe to infer ion adsorption, due to the ambiguity created by multiple effects, such as the hydration shell of the ions or interference effects. 30,[34][35] On the other hand, XFNTR cannot provide some details of ion distribution, because it is sensitive only to the total number of ions in both Stern and diffuse layers and insensitive to the reorganization of ions 4 between them. 28 Acknowledging the advantages and shortcomings of both methods allows elucidating the details of trivalent ion adsorption that cannot be determined by a single method.…”
mentioning
confidence: 99%
“…37 Studies with varying NaCl concentrations under AA monolayers have posited that the low signal in the water/AA system, which is comparable to a very high ionic strength system, is due to the destructive interference of SFG signal coming from the sample depth. 30,34 The persistence of OH signal at very high [NaCl] has been attributed to the finite size of the counterion (Na + ) which limits the charge screening when the Debye length is low. 37 With the addition of NdCl3 to the subphase, 3250 and 3550 cm -1 bands decrease gradually in contrast to the immediate decrease in the absence of the background salt (Figure 2b).…”
mentioning
confidence: 99%
“…It is reasonable to assume that stronger hydrogen bonded water populations are farther into the bulk and weaker hydrogen bonded water populations are closer to the surface [33]. Indeed, we suggest that the 3400 cm -1 population is very close to the surface and possibly interacting with the GO, and 3600 cm -1 peak originates from the water molecules mostly trapped between the GO sheets.…”
Section: Identifying Water Populations With Different Hydrogen Bondin...mentioning
confidence: 72%
“…Previous SFG studies of the GO/aqueous interface only covered the latter of this concentration range that shows the decreasing SFG signal [35]. A recent study at the silica/water interface using lower concentrations demonstrated a similar increasing and decreasing trend [33]. However, the overall SFG intensity showed stronger cation specific effects due to significantly different chemistry of the silica surface compared to GO.…”
Section: Interfacial Water Structures Depend On the Salt Concentrationmentioning
confidence: 88%
See 1 more Smart Citation